ASSESSMENT OF KNOWLEDGE AND AWARENESS REGARDING METABOLIC SYNDROME AND ITS COMPONENTS AMONG UNDERGRADUATE PHYSIOTHERAPY STUDENTS - NEHA, CHIGULAPALLI; DV, KRISHNA VENI; VEMURI, SOUNDARYA; SRAVYA REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to assess the level of knowledge and awareness about metabolic syndrome (Met S) and its components among the 1st year physiotherapy students and also the difference in the level of knowledge and awareness among male and female students. Methods: A self-administered structured questionnaire consisting of 90 questions about components of Met S was distributed among 38 students studying 1st year physiotherapy at Apollo College of Physiotherapy, Hyderabad, after obtaining a written consent from them. The data extracted were tabulated, statistically analyzed and results were obtained. Results: Physiotherapy students have good knowledge about types and causes of diabetes and poor knowledge about symptoms, biochemical process, and complications of Met S. They expressed poor knowledge to understand the link between hypertension and pregnancy. They could understand the role of hereditary factors only in diabetes but not in other components. Conclusion: Met S is a common disorder in the society; therefore, the awareness should be raised among the student population and as paramedics, it is their responsibility to communicate with the public about the risk factors and complications associated with it and counsel them to adopt a healthy lifestyle to protect themselves from the complications.